Homework Help

How do I factor this problem?14x^2-56

user profile pic

amgurly120 | Student, Grade 9 | eNotes Newbie

Posted April 30, 2009 at 7:41 AM via web

dislike 2 like

How do I factor this problem?

14x^2-56

6 Answers | Add Yours

user profile pic

jovona | Salutatorian

Posted April 30, 2009 at 7:47 AM (Answer #1)

dislike 1 like

14x^2-56 =

14(x^2-4) =

14(x-2)(x+2)

user profile pic

violy | High School Teacher | (Level 3) Assistant Educator

Posted January 4, 2013 at 4:39 AM (Answer #2)

dislike 1 like

First factor out the gcf (greatest common factor) which is 14:

14x^2 - 56 = 14(x^2 - 4) 

We use the Difference of Two Squares Formula, for x^2 - 4: 

a^2 - b^2 = (a - b)(a + b)

So, 

x^2 - 4 = (x - 2)(x + 2)

We will now have,

14x^2 - 56 = 14(x^2 - 4) = 14(x - 2)(x + 2)

Hence, factored form of 14x^2 - 56 = 14(x - 2)(x + 2).

user profile pic

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted January 27, 2013 at 5:28 PM (Answer #3)

dislike 1 like

You need to decompose the coefficients such that:

`14 = 1*2*7`

`56 = 1*2^3*7`

You need to write the expression using the factored form of coefficients, such that:

`2*7x^2 - 2^3*7`

You should notice that there exists the common factor `2*7` , hence, you may factor out `2*7` , such that:

`2*7(x^2 - 2^2)`

You need to convert the difference of squares `x^2 - 2^2` into a product, using the following formula, such that:

`a^2 - b^2 = (a-b)(a+b)`

Reasoning by analogy yields:

`x^2 - 2^2 = (x - 2)(x + 2)`

Hence, evaluating the factored form of the given expression, yields `14x^2 - 56 = 14(x - 2)(x + 2).`

user profile pic

atyourservice | TA , Grade 10 | Valedictorian

Posted May 30, 2014 at 12:51 AM (Answer #4)

dislike 0 like

14x^2-56

both 14 and 56 have a common factor of 14 so factor out 14

14 ( x^2 - 4 )

x^2 - 4 is known as the difference of 2 squares

difference of 2 squares =  (a - b)(a + b)

14 (x-2)(x+2)

user profile pic

fashionableb1 | Student, Grade 10 | Salutatorian

Posted May 30, 2014 at 3:20 AM (Answer #5)

dislike 0 like

14x^2-56 = 14(x^2-4) = 14(x-2)(x+2)

user profile pic

givingiswinning | Student, Grade 10 | Valedictorian

Posted August 16, 2014 at 12:28 AM (Answer #6)

dislike 0 like

14x^2-56 ==>

14(x^2-4) ==>

14(x-2)(x+2)

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes